Measuring the effect of electronic hearing protection devices on behavioral detection thresholds - Thompson, Eric R.; Gallagher, Hilary; Pryor, Nina (The Journal of the Acoustical Society of America, 2023)
Electronic hearing protection devices can provide amplification for quiet ambient sounds, while still providing protection against loud sounds. These can be important in environments with sporadic and unpredictable hazardous noise, but also with a need for maintaining awareness of ambient sounds, or for conducting face-to-face communication. This study’s aim was to understand what impact electronic hearing protection devices have on auditory detection thresholds. Human subjects were used to measure thresholds for narrowband noise bursts without hearing protection, with electronic hearing protectors powered off, and with electronic hearing protectors powered on with several gain settings. In addition, electroacoustic measurements were made of the input/output functions and electronic noise floors of the hearing protectors at the same gain settings. The data showed that thresholds in quiet with electronic hearing protectors were higher than without, regardless of the device amplification. This could be attributed to the hearing protector electronic noise limiting performance. Thresholds measured with ambient masking noise were similar across open ear and device conditions, reflecting that the signal-to-noise ratio for ambient sounds does not change with amplification. Listeners with a simulated conductive hearing loss had lower thresholds with an electronic hearing protector than without, suggesting a benefit of the device amplification.